Development of Islamic Economy through the Empowerment of Pesantren as Economically Independent Institutions in Indonesia - Fahmi, Reza; Aswirna, Prima (Journal of Islamic Economics (JoIE), 2023)
Introduction/Main Objectives: this study wants to illustrate: (1). Analyze the development of agricultural, plantation, fishery businesses managed by Islamic boarding schools. (2) Analyze obstacles and opportunities for entrepreneurial business development developed in pesantren. (3) Analyze possible solutions developed to improve the quality of entrepreneurship that has been developed by pesantren. Research Methods: This research uses a qualitative approach. In-depth interviews and observations as data collection methods. Data analysis uses the approach used by miles and hubermen. Results: The results of this study found that; First, the development of agricultural, plantation and fishery businesses in Islamic boarding schools is still very conventional. Second, the challenge that arises is to expand the market network to market business products. Third, "Marrying" agricultural business activities that have been developed with optimal technological development.  Conclusion: Broading up market with using internet will incease the income  of Islamic Boarding School as Self-fulfillment institution.